Glycerol carbonate in Ferrier reaction: Access to new enantiopure building blocks to develop glycoglycerolipid analogues. (21st December 2016) - da Costa, Pollyanna Leite Ferreira; Melo, Valentina Nascimento; Guimarães, Bruna Martins; Schuler, Marie; Pimenta, Vanessa; Rollin, Patrick; Tatibouët, Arnaud; de Oliveira, Ronaldo Nascimento
Abstract: Glycerol carbonate and tri- O -acetyl-D-glucal were used for the synthesis of glycero-functionalized carbohydrates. Ferrier reaction between the two partners afforded the O -glucoside in 84% yield. Spontaneous crystallization yielded 28% of a pure diastereoisomer with the S configuration as determined by X-ray crystallography. Then, the azido-glycerosugar was prepared in two steps: ring opening of the cyclic carbonate with sodium azide and per-acetylation with an excellent yield of 94%. A library of glycoconjugates were prepared using a 1, 3-dipolar cycloaddition in yields ranging from 64 to 99%. Graphical abstract: Highlights: New synthetic strategies based on Ferrier reaction and CuAAC were employed for the synthesis of new chemical entities. The new compounds were obtained as pure diastereoisomers as showed by NMR experiments and X-ray data. Renewable resources (D-glucose and glycerol) were used for the synthesis of a library of neo-glycoglycerolipid scaffolds.